2003
DOI: 10.1124/dmd.31.10.1269
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Pharmacokinetics of a Dipeptidyl Peptidase Iv Inhibitor in Rats, Dogs, and Monkeys With Selective Carbamoyl Glucuronidation of the Primary Amine in Dogs

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:The pharmacokinetics and metabolism of the L-threo isoleucine thiazolidide dipeptidyl peptidase IV inhibitor, di-[2S,3S]-2-amino-3-methyl-pentanoic-1,3-thiazolidine fumarate (ILT-threo) and its allo stereoisomer (ILT-allo) were evaluated in rats, dogs, and monkeys. Both compounds were well absorbed (>80%) in all species, and most of the dose (>60%) was recovered in urine. Metabolites identified in all species included a sulfoxide (M1), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…In addition to the common neutral loss of 176 Da (i.e., dehydrated glucuronic acid moiety) from the protonated molecular ion of regular glucuronide metabolites, a unique neutral loss of 220 Da (i.e., the sum of dehydrated glucuronic acid moiety and carbon dioxide, 176 ϩ 44 Da) from the protonated molecular ions of carbamoyl O-glucuronide metabolites has been frequently reported in the literature (Straub et al, 1988;Tremaine et al, 1989;Dow et al, 1994;Schaefer et al, 1998;Beconi et al, 2003). In this study, the fragments of m/z 247 and m/z 291 observed in the mass spectra of d-and l-milnacipran carbamoyl O-glucuronide metabolites support the occurrence of both types of neutral losses (220 and 176 Da) from the protonated molecular ions (m/z 467) of these metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the common neutral loss of 176 Da (i.e., dehydrated glucuronic acid moiety) from the protonated molecular ion of regular glucuronide metabolites, a unique neutral loss of 220 Da (i.e., the sum of dehydrated glucuronic acid moiety and carbon dioxide, 176 ϩ 44 Da) from the protonated molecular ions of carbamoyl O-glucuronide metabolites has been frequently reported in the literature (Straub et al, 1988;Tremaine et al, 1989;Dow et al, 1994;Schaefer et al, 1998;Beconi et al, 2003). In this study, the fragments of m/z 247 and m/z 291 observed in the mass spectra of d-and l-milnacipran carbamoyl O-glucuronide metabolites support the occurrence of both types of neutral losses (220 and 176 Da) from the protonated molecular ions (m/z 467) of these metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…at ASPET Journals on May 11, 2018 dmd.aspetjournals.org Downloaded from primary amine was reported for the dipeptidyl peptidase inhibitors L-threo isoleucine thiazolidide and its allo stereoisomer (Beconi et al, 2003) and seems to be common for a group of low molecular weight amino amides.…”
Section: Disposition Of Sitagliptin In Rats and Dogsmentioning
confidence: 99%
“…3) of m/z 628 produced sequential loss of glucuronic acid (176 amu) and carbon dioxide (44 amu) to give m/z of 452 and 408, respectively. This is a typical fragmentation pattern for a carbamoyl glucuronic acid conjugate (Liu and Pereira, 2002;Beconi et al, 2003). …”
Section: Disposition Of Sitagliptin In Rats and Dogsmentioning
confidence: 99%
“…The first, Ma, an N-carbamoyl glucuronide metabolite found in all species except humans, was presumably formed by reaction of the amine with dissolved CO 2 to form a transient carbamic acid intermediate, followed by subsequent conjugation with glucuronic acid. N-carbamoyl glucuronidation is an uncommon metabolic reaction but has been reported for several primary and secondary amines, including tocainide (Elvin et al, 1980), carvedilol (Schaefer, 1992), a dipeptidyl peptidase IV inhibitor ILT-threo (Beconi et al, 2003), and sertraline (Obach et al, 2005). In vitro formation of N-carbamoyl glucuronide metabolites have also been reported in liver microsomes incubated in a CO 2 -rich atmosphere and in carbonate buffer in the presence of UDP-GA. Obach et al (2005) have also reported that sertraline N-carbamoyl glucuronidation was primarily formed by UGT2B7.…”
Section: Discussionmentioning
confidence: 94%